The XVA of Financial Derivatives: CVA, DVA and FVA Explained - Lu, Dongsheng; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This latest addition to the Financial Engineering Explained series focuses on the new standards for derivatives valuation, namely, pricing and risk management taking into account counterparty risk, and the XVA's Credit, Funding and Debt value adjustments.
Keywords: Risk management; Banks and banking; Financial engineering; Investment banking; Securities; Risk Management; Banking; Financial Engineering; Investments and Securities